INVESTING IN THE GREEN ECONOMY: LEGAL REGULATION (American Journal of Business Management, Economics and Banking, 2023)
The article discusses the current state of legal regulation of investments in the green economy. Five key aspects are analyzed: incentives for green investment, removal of barriers, international cooperation, monitoring and enforcement mechanisms, and stakeholder engagement. A comprehensive framework is proposed to accelerate the transition by strengthening the rule of law, increasing policy coherence, implementing sound rules, investor confidence and institutional capacity-building. The new frameworks presented include the Green Investment Code, the Carbon Disclosure Regime, the Climate Justice Fund, and multi-stakeholder dialogues.